The Values of Islamic Education for Building Tolerance in the Jombang Community: A Qualitative Study of the Role of Religious Harmony Forum - Abidin, Achmad Anwar; Fatawi, Izzul; Kausar, Shakila (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The people of Jombang have proven their ability to coexist peacefully despite significant differences. However, with the emergence of increasing global challenges such as radicalism and intolerance, it is important to strengthen the foundations of tolerance through education. The integration of Islamic educational values has the potential to be an effective solution to face this challenge. This research aims to explore how the values of Islamic education can be integrated into the life of the people of Jombang and how it can strengthen tolerant behavior. This research was conducted in Jombang Regency, East Java Province, with the research subject of the Jombang Regency Religious Harmony Forum (FKUB) consisting of 17 interfaith and group figures. The research method used is qualitative research with an ethnographic approach. The integration of Islamic educational values in the life of the people of Jombang goes through four stages of process, namely, ta'aruf (knowing each other), tafahum (understanding each other), ta'awun (helping each other), and takafful (mutual guarantee), which is hierarchical. In addition, one important process covers the four stages, namely the ta'alum (mutual learning) process, which is carried out simultaneously with the four stages. From this study, it can be proven that the integration of Islamic educational values carried out by FKUB Jombang Regency has strengthened tolerant behavior, strengthened social bonds, and encouraged better community cohesion in the Jombang community.